Speech act taxonomy as a tool for ethnographic description : an analysis based on videotapes of continuous behavior in two New York households - Reiss, Nira (Pragmatics & beyond ;, 1985)
This study is intended to design measures for ethnographic description including speech acts in an etic instrumental approach, oriented toward an analysis of the functions of communicative events in relation to the ongoing stream of behavior. A revised taxonomy of speech acts is applied to an empirical corpus and is shown to produce a systematic set of behavioral measures which are potentially productive for cross-cultural comparison.